Metagenomic Analysis Reveals the Effects of Microplastics on Antibiotic Resistance Genes in Sludge Anaerobic Digestion - Zhonghong Li; Donghai Yuan (Toxics)
Sewage sludge is recognized as both a source and a reservoir for antibiotic resistance genes (ARGs). Within an anaerobic digestion (AD) system, the presence of microplastics (MPs) has been observed to potentially facilitate the proliferation of these ARGs. Understanding the influence of MPs on microbial behavior and horizontal gene transfer (HGT) within the AD system is crucial for effectively managing the dissemination of ARGs in the environment. This study utilized metagenomic approaches to analyze the dynamics of various types of ARGs and potential microbial mechanisms under exposure to MPs during the AD process. The findings indicated that MPs in the AD process can enhance the proliferation of ARGs, with the extent of this enhancement increasing with the dosage of MPs: polyethylene (PE), polyethylene terephthalate (PET), and polylactic acid (PLA) MPs increased the abundance of ARGs in the anaerobic digestion system by up to 29.90%, 18.64%, and 14.15%, respectively. Additionally, the presence of MPs increased the relative abundance of mobile genetic elements (MGEs) during the AD process. Network correlation analysis further revealed that plasmids represent the predominant category of MGEs involved in the HGT of ARGs. Propionibacterium and Alicycliphilus were identified as the primary potential hosts for these ARGs. The results of gene function annotation indicated that exposure to MPs led to an increased the relative abundance of genes related to the production of reactive oxygen species (ROS), alterations in membrane permeability, ATP synthesis, and the secretion of extracellular polymeric substances (EPS). These genes play crucial roles in influencing the HGT of ARGs.